2010
DOI: 10.1080/15287391003744807
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method Based on ICP-MS for Estimation of Background Levels of Arsenic, Cadmium, Copper, Manganese, Nickel, Lead, and Selenium in Blood of the Brazilian Population

Abstract: Throughout the world, biomonitoring has become the standard for assessing exposure of individuals to toxic elements as well as for responding to serious environmental public health problems. However, extensive biomonitoring surveys require rapid and simple analytical methods. Thus, a simple and high-throughput method is proposed for the determination of arsenic (As), cadmium (Cd), copper (Cu), manganese (Mn), nickel (Ni), lead (Pb), and selenium (Se) in blood samples by using inductively coupled plasma-mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
47
5
12

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(79 citation statements)
references
References 30 publications
15
47
5
12
Order By: Relevance
“…S4 showed a typical calibration curve for ICP-MS to measure lead in Coca-Cola, with a linear dynamic range of four orders of magnitude. Similar to EESI-MS n , the LODs for ICP-MS to measure lead in different samples were generally at the level of ppt or less, which fits well with previous studies [31,35,[65][66][67]. However, during ICP analysis, analytes, no matter whether they are organic or inorganic species, are usually broken down to elemental atoms for further mass spectrometric analysis or spectroscopic measurement.…”
Section: Direct and Semi-quantitative Measurement Using Eesisupporting
confidence: 84%
See 2 more Smart Citations
“…S4 showed a typical calibration curve for ICP-MS to measure lead in Coca-Cola, with a linear dynamic range of four orders of magnitude. Similar to EESI-MS n , the LODs for ICP-MS to measure lead in different samples were generally at the level of ppt or less, which fits well with previous studies [31,35,[65][66][67]. However, during ICP analysis, analytes, no matter whether they are organic or inorganic species, are usually broken down to elemental atoms for further mass spectrometric analysis or spectroscopic measurement.…”
Section: Direct and Semi-quantitative Measurement Using Eesisupporting
confidence: 84%
“…ICP-MS can be used to analyze metal compounds, but usually after extensive sample pretreatment [31,33]. Since ICP-MS is a classic method to detect lead [31,35,[65][66][67], we also performed quantitative analysis of lead in various samples using ICP-MS. It was found that the performance of EESI-MS n was comparable to that of ICP-MS for lead detection in samples with complex matrices.…”
Section: Direct and Semi-quantitative Measurement Using Eesimentioning
confidence: 99%
See 1 more Smart Citation
“…To date, many detection methods have been applied for detecting blood lead ions, and most are based on atomic absorption spectroscopy (AAS) 5 and inductively coupled plasma mass spectrometry. [6][7][8] However, these sensitive methods generally require expensive instruments, professional skill and complicated sample pretreatment, which may be limiting for the insite evaluation or monitoring of lead poisoning. Therefore, developing a simple, fast, sensitive, selective and field-deployable detection method for probing blood lead levels has become an interesting and attractive target to pursue.…”
mentioning
confidence: 99%
“…1,6 The analysis of trace elements in biological samples is predominantly performed using atomic spectrometry techniques, such as atomic absorption spectrometry (AAS), [15][16][17][18][19][20][21][22][23] inductively coupled plasma emission spectrometry (ICP-OES) 24 and inductively coupled plasma mass spectrometry (ICP-MS). [25][26][27][28][29] ICP-MS offers several advantages, including simultaneous multielement measurement capability coupled with very low limits of detection, a wider linear dynamic range, allowing the determination of major and trace elements at the same sample injection and isotopic information.…”
Section: Introductionmentioning
confidence: 99%